Answer:
x=(k√x)/(w^2)(cube√z)
x varies directly with square root of y is:
x = k √y
And inversely with the square of w and cube root of s is:
/(w^2)(cube√z)
Now put those together:
x=(k√x)/(w^2)(cube√z)
The formula is:
x=ky/wz but add the specific info like square, roots, or etc
Answer:
45°
Step-by-step explanation:
The base angle are the same measure and since one angle is already 90° the remaining two are 45°. They have to equal up to 180. 90 + 45 + 45 = 180.
Hope this helps ya!!
Answer: a= -18/2
Step-by-step explanation:
2a + 2x3 = -12
2a + 6 = -12
2a + 6 - 6 = -12 - 6 ( subtract 6 from both sides)
2a = -18 (Divide 2 by both sides)
a= -18/2
Answer:
90 degrees
Step-by-step explanation:
iiiiiiiiiiii
Answer:
I don't know. I need the whole question to answer.
Step-by-step explanation:
Sorry